The Nature of Consciousness in the Visually Deprived Brain - Kupers, Ron; Pietrini, Pietro; Ricciardi, Emiliano; Ptito, Maurice (Frontiers in Psychology, 2011)
Vision plays a central role in how we represent and interact with the world around us. The primacy of vision is structurally imbedded in cortical organization as about one third of the cortical surface in primates is involved in visual processes. Consequently, the loss of vision, either at birth or later in life, profoundly affects brain organization and the way the world is perceived and acted upon. In this paper, we address a number of issues on the nature of consciousness in people deprived of vision. Do brains from sighted and blind individuals differ, and how? How does the brain of someone who has never had any visual perception form an image of the external world? What is the subjective correlate of activity in the visual cortex of a subject who has never seen in life? More in general, what can we learn about the functional development of the human brain in physiological conditions by studying blindness? We discuss findings from animal research as well from recent psychophysical and functional brain imaging studies in sighted and blind individuals that shed some new light on the answers to these questions.